Social Impact and Challenges of Rehabilitation in Combating Drug Abuse in Indonesia - Riska Ramadani, Vivi (Dinasti Research, 2025)
The issue of narcotics in Indonesia is increasing, even though various prevention and enforcement efforts have been made, drug abuse is increasingly worrying, especially among the younger generation, this is due to easy access to obtain these illicit goods, in this article the aim is to discuss the effectiveness of the law, social impacts, rehabilitation and challenges in law enforcement in narcotics cases.